The heart of the wild essays on nature, conservation, and the human future (Princeton University Press, 2024)
"How do we keep a love of nature and the wild alive in our increasingly human-dominated world? According to the scientists and writers in this book, doing so is of paramount significance; however, the answer is not necessarily blanket preservation of wild places, which is increasingly unrealistic. Rather, the answer to "how to care for nature" is more nuanced and often entails acceptance of a broader definition of wild as well and what it means to experience nature. This book will be divided into two parts. In the first part, authors will explore and complicate what wildness means. For example, science writer Emma Marris argues that spontaneous vegetation and free-roaming animals in cities actually possess more autonomy than the wolves or pines of Yellowstone; biologist Jonathan Losos asks whether invasive species are necessarily detrimental and may even play a role in restoring ecosystems; and psychologist Susan Clayton discusses new ways of experiencing nature, particularly via technology, and what the benefits and limitations may be. In the second half of the book, essays will reflect on the roles of naturalism, natural history, and nature education & communication in helping us connect with wild species and landscapes at a time when many of those connections have frayed or even lost altogether"--
Includes bibliographical references and index
Keywords: Nature; Wildlife conservation; Human ecology; Social ecology; Faune / Protection; Écologie humaine; Écologie sociale; human ecology; NATURE / Essays; SCIENCE / Life Sciences / Biology; Essays